Preparation, Characterization, and Immuno-Enhancing Activity of Polysaccharides from Glycyrrhiza uralensis - Aipire, Adila (Biomolecules, 2020)
Glycyrrhiza uralensis is a Chinese herbal medicine with various bioactivities. Three fractions (GUPS-I, GUPS-II and GUPS-III) of G. uralensis polysaccharides (GUPS) were obtained with molecular weights of 1.06, 29.1, and 14.9 kDa, respectively. The monosaccharide compositions of GUPS-II and GUPS-III were similar, while that of GUPS-I was distinctively different. The results of scanning electron microscopy, FT-IR, and NMR suggested that GUPS-II and GUPS-III were flaky with a smooth surface and contained α- and β-glycosidic linkages, while GUPS-I was granulated and contained only α-glycosidic linkages. Moreover, GUPS-II and GUPS-III exhibited better bioactivities on the maturation and cytokine production of dendritic cells (DCs) in vitro than that of GUPS-I. An in vivo experiment showed that only GUPS-II significantly enhanced the maturation of DCs. These results indicate that GUPS-II has the potential to be used in combination with cancer immunotherapy to enhance the therapeutic effect.